2014
DOI: 10.1371/journal.pone.0096100
|View full text |Cite
|
Sign up to set email alerts
|

Protein Thermodynamics Can Be Predicted Directly from Biological Growth Rates

Abstract: Life on Earth is capable of growing from temperatures well below freezing to above the boiling point of water, with some organisms preferring cooler and others hotter conditions. The growth rate of each organism ultimately depends on its intracellular chemical reactions. Here we show that a thermodynamic model based on a single, rate-limiting, enzyme-catalysed reaction accurately describes population growth rates in 230 diverse strains of unicellular and multicellular organisms. Collectively these represent al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 92 publications
5
41
0
Order By: Relevance
“…Second, even if Arrhenius is comparable to MMRT in a narrow temperature range, E A fails to capture key phenomenological features of temperature sensitivity in soil biological systems. Other non-linear models have also been shown to give suitable empirical fits to the temperature dependence of enzyme activity (Peterson et al, 2004; Del Grosso et al, 2005; Daniel and Danson, 2013; Corkrey et al, 2014), but MMRT not only fits well empirically, but is derived from thermodynamic theory and thus has an underlying theoretical basis. Thus, even if E A continues to be used in the future, E A values should not be taken as true indicators of temperature sensitivity, at least for soil extracellular enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Second, even if Arrhenius is comparable to MMRT in a narrow temperature range, E A fails to capture key phenomenological features of temperature sensitivity in soil biological systems. Other non-linear models have also been shown to give suitable empirical fits to the temperature dependence of enzyme activity (Peterson et al, 2004; Del Grosso et al, 2005; Daniel and Danson, 2013; Corkrey et al, 2014), but MMRT not only fits well empirically, but is derived from thermodynamic theory and thus has an underlying theoretical basis. Thus, even if E A continues to be used in the future, E A values should not be taken as true indicators of temperature sensitivity, at least for soil extracellular enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the rate of increase in performance with temperature necessarily slows down as T pk approaches. A solution to reduce this effect is to fit a full unimodal model to data using nonlinear regression (Schoolfield et al 1981;Ratkowsky et al 1983;Dell et al 2011;Barneche et al 2014), possibly combined with Bayesian inference of the error distribution of the estimated parameter (Corkrey et al 2012(Corkrey et al , 2014Barneche et al 2014;Johnson et al 2015). However, due to logistical reasons, sampling full, unimodal thermal responses is often not possible.…”
Section: E000 the American Naturalistmentioning
confidence: 99%
“…This may be interpreted as a greater agnosticism of the DEB toward whether E indeed reflects the activation energy of one or more ratelimiting enzymes in the underlying metabolic pathways. Indeed, whether the thermal sensitivities of biological traits truly reflect an activation energy remains a contentious issue (Clarke 2004;Gillooly et al 2006;del Rio 2008;Hobbs et al 2013;Corkrey et al 2014). Use of the BA model in ecology has also been criticized, because recent empirical studies have revealed a much wider range of E values (Irlich et al 2009; Knies and Kingsolver 2010;Dell et al 2011;Englund et al 2011) than the 0.6 eV (or sometimes 0.65 eV) originally suggested (Gillooly et al 2001) and which has subsequently so often been used in theoretical studies Vasseur and McCann 2005;Wolfshaar et al 2008;Petchey et al 2010;Rall et al 2010;O'Connor et al 2011;Stegen et al 2012).…”
mentioning
confidence: 99%
“…Many mines in British Columbia are located at high elevations and at northern latitudes, where it is particularly challenging to make biological treatment effective in the cold winter months. Kinetics of biological reactions and microbial growth are influenced by temperature according to a consistent expression that takes into account Arrhenius-type rate dependency on temperature and protein denaturation at below and above optimum temperatures for maximum growth [26]. It is thought that growth within different temperature regimes (psychrophilic, mesophilic and thermophilic) is determined by adaptation and not by taxonomy [26].…”
Section: Environmental Factors Influencing Microbial Population Strucmentioning
confidence: 99%
“…Kinetics of biological reactions and microbial growth are influenced by temperature according to a consistent expression that takes into account Arrhenius-type rate dependency on temperature and protein denaturation at below and above optimum temperatures for maximum growth [26]. It is thought that growth within different temperature regimes (psychrophilic, mesophilic and thermophilic) is determined by adaptation and not by taxonomy [26]. Our work supports this notion in that the microbial population composition of the bioreactor did not vary with temperature in a statistically significant way.…”
Section: Environmental Factors Influencing Microbial Population Strucmentioning
confidence: 99%